História da Escolinha de Artes do Centro de Artes e Letras da Universidade Federal de Santa Maria/RS - Benetti, Téoura (2007)
This study it was carried through in the Line of Research Education and Arts of the Post Graduation Education Program of the Universidade Federal de Santa Maria. It presents the history of the Escolinha de Artes/UFSM, Santa Maria, and supports in the necessity of knowing this history that it comes developing in Art/Education area for more than fourty years ago in the way contextualized before the modern and contemporary tendences of the Art teaching. The objectives had been to reconstruct the histiry of the Escolinha de Artes do Centro de Artes e Letras of Universidade Federal de Santa Maria with the transformation suffered by it through the time and contextualized its inside bigger scene that is of the Art/Education and of the Movement Escolinhas de Arte. In this historic contextualization are bring references about importance of the history, historiography in memory as a historic source on the basis of authors as DIEHL(2002), CAMBI(1999), NÓVOA(1995), looking for to point out the historiography tendences inside a contemporary view with MORIN(2003) and SANTOS(2002). To initiate the history of the Art/Education were carried one synthesis of the historic events that had led to the modern and contemporary contexts of the Art/Education in Brazil, where the main reference of research be in the work of BARBOSA(1978, 1982, 1984, 1986, 1994, 1997, 2003). Thus it is arrived at the context of the Movement Escolinhas de Arte where be considered the creation of the Escolinha de Arte of Brazil, the development of the Escolinhas and its repercussion on Brazilian Art/Educational field. In this stage the main references had been RODRIGUES(1972, 1980), VARELA(1972, 1986, 1988) and AZEVEDO(2001, 2003). The research of history of the Escolinha happened as a qualitative boarding having as reserach sources the quantity of documents and images of the Escolinha and interviews with three Art/Educators that had participated of history of the Escolinha in distinct times. Thus they had collaboreted with its memories Lia Maria Cechella Achutti, José Francisco Goulart and Elza Hirata. The interviews in depth can be characterized as opened and halfstructuralized. To deepen the studies on these methodological questions the main references had been MINAYO(1994), BOGDAN(1994), BIKLEN(2002) and GASKEL(2002). The instruments used for collection of data had been, of this form, the documents analysis, images of register and the qualitative interview. The greater result of investigation it was constitute of history of the Escolinha de Artes do Centro de Artes e Letras, until inexistent today, being this the greater contribute for Art/Education, constructed on the basis of the interviews and analysis of the documents as articles, statutes, planning, projects and images of the Laboratory of Initiation and Creativity in Arts (the Escolinha). This research shows as had been the activities and historical transformations of the Escolinha since its creation, the envolvement of professionals with conceive of the Movement Escolinha de Artes, the transformations occured and the link with the courses of the Department of Visual Arts, Music and Theater of Universidade Federal de Santa Maria